Capacity assessment and design of CFRP-strengthened steel channel columns - Kalavagunta S.; Naganathan S.; Mustapha K.N.B. (2023)
This paper presents a design method (BS5950-5) to predict the allowable load carrying capacity of cold formed steel channel section strengthened by carbon fiber reformed polymer composites applied to the web of the beam. A specimen is presented to illustrate the proposed design approach. The validity of the proposed design method has been verified by comparing with the experimental test results. A series of compression tests were conducted on plain and CFRP strengthened steel sections of different geometries. This paper also contains the consequences obtained by comparing the strengths of plain and CFRP strengthened steel columns using compression test. The findings showed that the strength of CFRP strengthened steel columns were up to 10% greater than plain cold form steel sections.